2015
DOI: 10.15226/jdodt.2015.00135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Myofunctional Therapy on Upper Intercanine Distance

Abstract: Objectives: The study was designed to investigate the correlation between myofunctional exercises, including repositioning of the tongue onto the palate and changes in intercanine distance of the upper jaw in non-growing patients. Methods:In this retrospective study a total of 141 women and men above the age of 18, treated by the Coulson Institute of Orofacial Myology, with no simultaneous orthodontic therapy, were included. All subjects have participated in a myofunctional therapy program for at least 8 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The NOI implemented in this study was mainly composed of guidance of the tongue position and behaviour shaping with positive reinforcement. To guide the tongue tip to rest close to the incisive papilla, a small hole‐punched stomahesive wafer with a diameter of 5 mm was placed on and attached to the wiped incisive papilla ( Figure a,b ). Children were trained to carry out the procedure three times per day with parents' supervision and assistance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The NOI implemented in this study was mainly composed of guidance of the tongue position and behaviour shaping with positive reinforcement. To guide the tongue tip to rest close to the incisive papilla, a small hole‐punched stomahesive wafer with a diameter of 5 mm was placed on and attached to the wiped incisive papilla ( Figure a,b ). Children were trained to carry out the procedure three times per day with parents' supervision and assistance.…”
Section: Methodsmentioning
confidence: 99%
“…The spot of stomahesive wafer eventually melted and peeled off without being aspirated or causing harm. Indeed, this material has been safely and widely used in medical and dental practice, as well as in the food industry. Guidance of the tongue position though use of a stomahesive wafer spot was accompanied by a behaviour‐shaping programme, which involved recording positive behaviour on reward charts and regular telephone calls from patients and parents to a trained orofacial myologist and dental hygienist.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Furthermore, it has been shown that changes in the dental formation can be influenced by myofunctional therapy even in non-growing patients. 6 Prefabricated unctional appliances have demonstrated to produce favorable outcomes in children mainly with Class II, division 1 malocclusion. 7,8 Myobrace® appliances are prefabricated functional appliances with tooth positioning and myofunctional training characteristics, which are used to correct malocclusions in the developing child, in conjunction with myofunctional therapy-through the Myobrace Activities™ protocol.…”
Section: Introductionmentioning
confidence: 99%